Comparative Genomic Analysis of a Clinical Isolate of Klebsiella quasipneumoniae subsp. similipneumoniae, a KPC-2 and OKP-B-6 Beta-Lactamases Producer Harboring Two Drug-Resistance Plasmids from Southeast Brazil - Nicolás, Marisa F.; Ramos, Pablo Ivan Pereira; Marques de Carvalho, Fabíola; Camargo, Dhian R. A.; de Fátima Morais Alves, Carlene; Loss de Morais, Guilherme; Almeida, Luiz G. P.; Souza, Rangel C.; Ciapina, Luciane P.; Vicente, Ana C. P.; Coimbra, Roney S.; Ribeiro de Vasconcelos, Ana T. (Frontiers in Microbiology, 2018)
The aim of this study was to unravel the genetic determinants responsible for multidrug (including carbapenems) resistance and virulence in a clinical isolate of Klebsiella quasipneumoniae subsp. similipneumoniae by whole-genome sequencing and comparative analyses. Eighty-three clinical isolates initially identified as carbapenem-resistant K. pneumoniae were collected from nosocomial infections in southeast Brazil. After RAPD screening, the KPC-142 isolate, showing the most divergent DNA pattern, was selected for complete genome sequencing in an Illumina HiSeq 2500 instrument. Reads were assembled into scaffolds, gaps between scaffolds were resolved by in silico gap filling and extensive bioinformatics analyses were performed, using multiple comparative analysis tools and databases. Genome sequencing allowed to correct the classification of the KPC-142 isolate as K. quasipneumoniae subsp. similipneumoniae. To the best of our knowledge this is the first complete genome reported to date of a clinical isolate of this subspecies harbouring both class A beta-lactamases KPC-2 and OKP-B-6 from South America. KPC-142 has one 5.2 Mbp chromosome (57.8% G+C) and two plasmids: 190 Kbp pKQPS142a (50.7% G+C) and 11 Kbp pKQPS142b (57.3% G+C). The 3 Kbp region in pKQPS142b containing the blaKPC-2 was highly similar to that of pKp13d of K. pneumoniae Kp13 isolated in Southern Brazil in 2009, suggesting the horizontal transfer of this resistance gene between different species of Klebsiella. KPC-142 additionally harbors an integrative conjugative element ICEPm1 that could be involved in the mobilization of pKQPS142b and determinants of resistance to other classes of antimicrobials, including aminoglycoside and silver. We present the completely assembled genome sequence of a clinical isolate of K. quasipneumoniae subsp. similipneumoniae, a KPC-2 and OKP-B-6 beta-lactamases producer and discuss the most relevant genomic features of this important resistant pathogen in comparison to several strains belonging to K. quasipneumoniae subsp. similipneumoniae (phylogroup II-B), K. quasipneumoniae subsp. quasipneumoniae (phylogroup II-A), K. pneumoniae (phylogroup I) and K. variicola (phylogroup III). Our study contributes to the description of the characteristics of a novel K. quasipneumoniae subsp. similipneumoniae strain circulating in South America that currently represent a serious potential risk for nosocomial settings.